Juridical Analysis of Digital Tax Policies in Facing the Global Economy - Judijanto , Loso (Journal of Scientific Insights, 2025)
This study examines the juridical frameworks and legal challenges surrounding digital tax policies as nations attempt to adapt their fiscal regulations to the rapidly evolving global digital economy. Using qualitative descriptive research methodology with a library research approach, this paper analyzes the legal foundations, international tax principles, and policy innovations that shape digital taxation. The research explores how jurisdictions worldwide are addressing tax base erosion, profit shifting, and value creation in digital business models while navigating sovereignty concerns and cross-border enforcement challenges. Findings indicate significant juridical tensions between traditional territorial tax principles and the borderless nature of digital commerce, with emerging legal approaches ranging from unilateral digital services taxes to multilateral framework agreements. The study concludes that effective digital tax regimes require both domestic legislative innovation and international legal harmonization to balance fiscal sovereignty with the practical realities of the global digital marketplace.